One-loop conformal invariance of the type II pure spinor superstring in a curved background - Bedoya, Oscar A. [UNESP]; Chandía, Osvaldo (Springer Nature, 2007)
We compute the one-loop beta functions for the Type II superstring using the pure spinor formalism in a generic supergravity background. It is known that the classical pure spinor BRST symmetry puts the background fields on-shell. In this paper we show that the one-loop beta functions vanish as a consequence of the classical BRST symmetry of the action. © SISSA 2007.
Keywords: Anomalies in field and string theories; Conformal field models in string theory